Effect of calcination temperature on friction and wear behavior of α–alumina (α‐Al2O3) for biomedical applications. Issue 2 (12th October 2018) - Fellah, Mamoun; Aissani, Linda; Abdul Samad, Mohammed; Prakasam, Mythili; Purnama, Agung; Montagne, Alex; IOST, Alain; Mejias, Alberto; Kossman, Stephania
Abstract: In this study, structural evolution, sliding friction, and wear behavior of the nano‐sized alpha‐alumina ( α ‐Al2 O3 ), synthesized by calcination of gibbsite (Al2 (OH)6 ) at different temperatures (273‐1473 K) are reported using X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), Scanning electron microscopy (SEM), and ball‐on‐disk wear tests. The effect of calcination temperature and the correlation between grain size, mechanical properties, and tribological behavior of the compounds are investigated. After calcination at 1473 K, the crystallite size of calcined and sintered alumina ( α ‐Al2 O3 ) compacts is as small as 10 nm. Also, it is observed that the average particle and grain size significantly affect the tribological properties of the compounds. At all the applied loads of 2, 8, and 16 N, respectively, the sliding wear rate and coefficient of friction were lower in the alumina compacts calcined at 1473 K. The improved tribological properties are attributed to the finer microstructure resulting in enhanced hardness of the sintered compacts calcined at 1473 K.